2017
DOI: 10.18632/oncotarget.20982
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 6 inhibition counteracts the epithelial-mesenchymal transition of peritoneal mesothelial cells and prevents peritoneal fibrosis

Abstract: The role of histone deacetylase 6 (HDAC6) in peritoneal fibrosis remains unknown. In this study, we examined the effect of HDAC6 inhibition on the epithelial–mesenchymal transition (EMT) of peritoneal mesothelial cells and development of peritoneal fibrosis. Treatment with tubastatin A, a highly selective HDAC6 inhibitor, or silencing of HDAC6 with siRNA inhibited transforming growth factor β1-induced EMT, as evidenced by decreased expression of α-smooth muscle actin, collagen I and preserved expression of E-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…To our knowledge, our study first deals on the effect of HDAC1 inhibition on MMT of MCs. A recent report analyzed the role of a selective HDAC6 inhibitor, tubastatin, in the inhibition of peritoneal MMT and fibrosis 29 . Interestingly, in apparent contradiction to our results, treatment with the inhibitor of histone acetyltransferase C646 was reported to limit the MMT induced by glucose in a MC line 30 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study first deals on the effect of HDAC1 inhibition on MMT of MCs. A recent report analyzed the role of a selective HDAC6 inhibitor, tubastatin, in the inhibition of peritoneal MMT and fibrosis 29 . Interestingly, in apparent contradiction to our results, treatment with the inhibitor of histone acetyltransferase C646 was reported to limit the MMT induced by glucose in a MC line 30 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that inhibition of class I HDACs with MS-275 or of Sirt1 and 2 with sirtinol inhibits renal fibroblast activation and attenuates renal fibrosis (23,24). Recently, studies in our laboratories and others have also indicated that the administration of tubastatin A, a selective inhibitor of HDAC6, was effective in blocking peritoneal and renal fibrosis (25,26). Moreover, Wang et al (27) have shown that HDAC4, an isoform of class IIa HDACs, contributes to podocyte injury in a murine model of diabetic nephropathy.…”
mentioning
confidence: 99%
“…Research groups have linked HDAC6 overexpression to organ fibrosis including the lung, kidney, and peritoneum (37,38). TGF β/Smad signaling is a key player in regulating renal fibrosis via the activation of Smad2 and Smad3 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…TGF β1induced epithelial mesenchymal transition is associated with HDAC6 dependent deacetylation of α tubulin (40,41). HDAC6 silencing inhibits TGF β1 induced E cadherin loss and collagen I expression (38). Korfei and colleagues (37) suggested that upregulation of HDAC6 in idiopathic pulmonary fibrosis was associated with fibroblast proliferation, fibroblast to myofibroblast differentiation and myofibroblast resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%